2015
DOI: 10.1038/ncomms9053
|View full text |Cite
|
Sign up to set email alerts
|

Signature of magnetic-dependent gapless odd frequency states at superconductor/ferromagnet interfaces

Abstract: The theory of superconductivity developed by Bardeen, Cooper and Schrieffer (BCS) explains the stabilization of electron pairs into a spin-singlet, even frequency, state by the formation of an energy gap within which the density of states is zero. At a superconductor interface with an inhomogeneous ferromagnet, a gapless odd frequency superconducting state is predicted, in which the Cooper pairs are in a spin-triplet state. Although indirect evidence for such a state has been obtained, the gap structure and pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 41 publications
11
137
2
1
Order By: Relevance
“…This behaviour is quite different to its neighbour in the periodic table holmium, which in thin films saturates in-plane at fields of typically only 300 mT, after which the squareness of its hysteresis loop suggest a long-ranged ferromagnetic ordering takes over and spiral magnetism does not reform [18,20]. This difference is most likely due to the c-axis crystalline anisotropy in the hcp structure being more important, or certainly being retained to a greater extent, in thin film Er.…”
Section: Magnetic Characterisationcontrasting
confidence: 65%
“…This behaviour is quite different to its neighbour in the periodic table holmium, which in thin films saturates in-plane at fields of typically only 300 mT, after which the squareness of its hysteresis loop suggest a long-ranged ferromagnetic ordering takes over and spiral magnetism does not reform [18,20]. This difference is most likely due to the c-axis crystalline anisotropy in the hcp structure being more important, or certainly being retained to a greater extent, in thin film Er.…”
Section: Magnetic Characterisationcontrasting
confidence: 65%
“…In addition to theoretical studies, there are experimental indications of the realization of odd-ω pairing at the interface of Nb thin films and epitaxial Ho 25 . Furthermore, the concept of odd-ω order parameters can be generalized to charge and spin density waves 26,27 and Majorana fermion pairs 28 , demonstrating the pervasiveness of the odd-ω class of ordered states.…”
Section: Introductionmentioning
confidence: 99%
“…[34]. Even though signals for the experimental verification of odd-frequency states are often discussed in connection to systems which explicitly break time-reversal symmetry [31][32][33], our paper reveals that odd-frequency solutions do not require a time-reversal breaking potential. Oddfrequency solutions can arise naturally for a time-reversal symmetric interaction as a symmetry-breaking ground state of a many-particle system with time-reversal invariant interactions.…”
Section: Resultsmentioning
confidence: 95%
“…Also, odd-frequency states were discussed in connection to time-reversal topological superconductivity in double Rashba wires, where it was found that odd-frequency pairing is strongly enhanced in the topological state [30]. For some of the above mentioned systems, the respective signatures of odd-frequency correlations could also be verified experimentally [31][32][33][34]. An extensive discussion of edge-states and topology in superconductors including odd-frequency gap functions was communicated by Tanaka, Sato and Nagaosa [35].…”
mentioning
confidence: 94%